Expression of CCCTC‐binding factor (CTCF) is linked to poor prognosis in prostate cancer. Issue 1 (29th November 2019) - Höflmayer, Doris; Steinhoff, Amélie; Hube‐Magg, Claudia; Kluth, Martina; Simon, Ronald; Burandt, Eike; Tsourlakis, Maria Christina; Minner, Sarah; Sauter, Guido; Büscheck, Franziska; Wilczak, Waldemar; Steurer, Stefan; et al.
Abstract : The chromatin‐organizing factor CCCTC‐binding factor (CTCF) is involved in transcriptional regulation, DNA‐loop formation, and telomere maintenance. To evaluate the clinical impact of CTCF in prostate cancer, we analyzed CTCF expression by immunohistochemistry on a tissue microarray containing 17 747 prostate cancers. Normal prostate tissue showed negative to low CTCF expression, while in prostate cancers, CTCF expression was seen in 7726 of our 12 555 (61.5%) tumors and was considered low in 44.6% and high in 17% of cancers. Particularly, high CTCF expression was significantly associated with the presence of the transmembrane protease, serine 2:ETS‐related gene fusion: Only 10% of ERG‐negative cancers, but 30% of ERG‐positive cancers had high‐level CTCF expression ( P  < 0.0001). CTCF expression was significantly associated with advanced pathological tumor stage, high Gleason grade ( P  < 0.0001 each), nodal metastasis ( P  = 0.0122), and early biochemical recurrence ( P  < 0.0001). Multivariable modeling revealed that the prognostic impact of CTCF was independent from established presurgical parameters such as clinical stage and Gleason grade of the biopsy. Comparison with key molecular alterations showed strong associations with the expression of the Ki‐67 proliferation marker and presence of phosphatase and tensin homolog deletions ( P  < 0.0001 each). The results of our study identify CTCF expression as a candidate biomarker for prognosis assessment in prostate cancer. Abstract : The transcriptional repressor CCCTC‐binding factor, which is involved in modeling the chromatin face in the nucleus of a cell, was analyzed for its expression in prostate cancer. We report here that its upregulation was associated with a shorter prostate‐specific antigen recurrence‐free survival after prostatectomy in a large cohort of prostate cancer patients.